tkl is the avian homolog of the mammalian lck tyrosine protein kinase gene. - Chow, L M (1992)
We have tested the possibility that tkl, a partially characterized avian tyrosine protein kinase gene, is the chicken homolog of lck, a lymphocyte-specific mammalian gene. Using polymerase chain reactions, we have cloned sequences encoding the previously unidentified amino terminus of the tkl gene product. The newly defined unique domain of Tkl displayed significant identity (68%) to the equivalent region of the mammalian lck gene product, p56lck. This identity included a glycine residue at position 2 (present in all Scr-related tyrosine protein kinases) and a cysteine motif at positions 20 and 23, which allows binding of p56lck to CD4 and CD8 in mammalian T lymphocytes. A specific RNase protection assay revealed that, in contrast to a previous report (K. Strebhardt, J. I. Mullins, C. Bruck, and H. Rübsamen-Waigmann, Proc. Natl. Acad. Sci. USA 84:8778-8782, 1987), tkl expression is restricted to the lymphoid tissues thymus and spleen. Moreover, the absence of tkl transcripts in the bursa of Fabricius suggested that this gene is expressed in avian T lymphocytes but not in B lymphocytes. A polyclonal rabbit antiserum raised against the unique domain of Tkl recognized a 56-kDa polypeptide with associated protein kinase activity from avian thymus-derived cells. Additional studies showed that p56tkl is structurally similar to mammalian p56lck and that it is physically associated with the avian CD4 and CD8 T-cell surface antigens. It was also determined that tkl transcripts have one major type of 5' untranslated region (UTR), which differs greatly from the two known 5' UTRs of mammalian lck mRNAs.(ABSTRACT TRUNCATED AT 250 WORDS)